Spectrophotometric Determination of frusemide in Some Pharmaceutical via Oxidative Coupling Reaction - Fawaz. Ibrahim; Neif Ahmad (مجلة التربية والعلم, 2006)
A simple and accurate spectrophotometric method has been described for the determination of frusemide in pharmaceutical preparation. The method is based on oxidative coupling reaction of frusemide with promethazine in aqueous acidic solution in the presence of hypochlorite ion and the absorbance of the blue product was measured at 625 nm against a reagent blank. The blue color formed immediately and stable for at least 24h. Calibration graph was rectinlinear for 2-20 ppm. The molar absorptivity is 0.625104.mol-1.cm-1, relative standard .